Adiponectin Upregulates MiR-133a in Cardiac Hypertrophy through AMPK Activation and Reduced ERK1/2 Phosphorylation. - Ying Li; Xiaojun Cai; Yuqing Guan; Lei Wang; Shuya Wang; Yueyan Li; Ying Fu; Xiaoyuan Gao; Guohai Su (PLoS ONE, 2016)
Adiponectin and miR-133a are key regulators in cardiac hypertrophy. However, whether APN has a potential effect on miR-133a remains unclear. In this study, we aimed to investigate whether APN could regulate miR-133a expression in Angiotensin II (Ang II) induced cardiac hypertrophy in vivo and in vitro. Lentiviral-mediated adiponectin treatment attenuated cardiac hypertrophy induced by Ang II infusion in male wistar rats as determined by reduced cell surface area and mRNA levels of atrial natriuretic peptide (ANF) and brain natriuretic peptide (BNP), also the reduced left ventricular end-diastolic posterior wall thickness (LVPWd) and end-diastolic interventricular septal thickness (IVSd). Meanwhile, APN elevated miR-133a level which was downregulated by Ang II. To further investigate the underlying molecular mechanisms, we treated neonatal rat ventricular myocytes (NRVMs) with recombinant rat APN before Ang II stimulation. Pretreating cells with recombinant APN promoted AMP-activated protein kinase (AMPK) phosphorylation and inhibited ERK activation. By using the inhibitor of AMPK or a lentiviral vector expressing AMPK short hairpin RNA (shRNA) cancelled the positive effect of APN on miR-133a. The ERK inhibitor PD98059 reversed the downregulation of miR-133a induced by Ang II. These results indicated that the AMPK activation and ERK inhibition were responsible for the positive effect of APN on miR-133a. Furthermore, adiponectin receptor 1 (AdipoR1) mRNA expression was inhibited by Ang II stimulation. The positive effects of APN on AMPK activation and miR-133a, and the inhibitory effect on ERK phosphorylation were inhibited in NRVMs transfected with lentiviral AdipoR1shRNA. In addition, APN depressed the elevated expression of connective tissue growth factor (CTGF), a direct target of miR-133a, through the AMPK pathway. Taken together, our data indicated that APN reversed miR-133a levels through AMPK activation, reduced ERK1/2 phosphorylation in cardiomyocytes stimulated with Ang II, revealing a previously undemonstrated and important link between APN and miR-133a.